SPLIT PERSONALITY OF ROBERT FORD IN ANDREW DOMINIK‟STHE ASSASSINATION OF JESSE JAMES BY THE COWARD ROBERT FORD MOVIE: A PSYCHOANALYTIC APPROACH - ANGGANI, FAJAR AFRI (2011)
The major problem of this study is how Robert Ford split his personality reflected in Andrew Dominik's The Assassination of Jesse James by the Coward Robert Ford, resulted from unhandled problem he encounters. The aim of this study is to reveal the personality structure and the split of personality of the major character, influencing his behavior, using the mean of structural and psychoanalytic analysis. The object of this study is The Assassination of Jesse James by the Coward Robert Ford and it is focused on one of the major characters, namely Robert Ford.The benefit of the study is to give some contributions in the application of psychoanalytic approach in literary study and to fulfill the requirement for getting bachelor degree in English department. This study uses library data. The primary data are taken from the movie itself, while the secondary data from some criticism and information needed. The method of data collection is description and the study employs Sigmund Freud's psychoanalysis to answer the problem. The finding of the study shows that the problem that the major character encounters causes the conflicts of his mental condition. Then, it develops to be his split personality. He does some actions to overcome his split personality. All of his acts are included into ego. These ways are the effective ways to overcome the problem.